Determination of cobalt in some plants by reversed-phase high performance liquid chromatography - Ciftci, Harun (Asian Journal of Chemistry, 2008)
The separation and determination of cobalt chelate with 4-(2-pyridylazo)resorcinol (PAR) by reversed-phase HPLC was investigated. The Co(III)-PAR chelate was separated on a C,x siloxane bonded phase and eluted within 5.4 min with methanol-water-acetonitrile (1 x 10(-2) mol L-1) and sodium acetate (55:40:2.5:2.5 v/v) containing 5 x 10(-3) mol L-1 ethylenedi-aminetatraacetic acid (EDTA) (pH 7.5). The detection limits of Co(III) at 520 nm are 1.2 mu g L-1. The method was applied to the determination of cobalt in some samples of plants. The contents of cobalt in the plants samples were found in the ranges, 0.941-0.141 mg/kg (dry matter). Rosa canina is rather rich in cobalt and is recommended as a source.
Keywords: HPLC; 4-(2-pyridylazo)resorcinol; UV-Visible; cobalt; PAR; resorcinol; Rosa canina